Applied research note: Black Soldier Fly Larvae Frass is an effective feed ingredient for broiler diets - D.S. Adams; E.A. Koutsos (Journal of Applied Poultry Research)
SUMMARY: Black Soldier Fly Larvae (BSFL) have been successfully utilized in the diets of noncommercial poultry flocks for many years. Availability and cost have hindered its adoption by commercial poultry producers. Frass, a production byproduct, comprising exoskeletons, small larvae, digested feed, and leftover feedstock has predominately been used as fertilizer. The nutrient content of frass makes it appropriate for use in animal feed, and BSFL frass is produced at a volume and cost that is viable for commercial poultry producers. This product contains lauric acid, chitin, and antimicrobial peptides, which may improve overall animal health. In this study, two experiments were conducted to examine the impact of BSFL Frass inclusion in broiler diets on growth performance compared to a control diet.Diets in this study were formulated to be isonitrogenous and isocaloric. Frass from BSFL was included at 2.5 % in the starter phase, 5.0 % in the grower phase, and 10 % in the finisher phase. Both experiments utilized 10 replicates per treatment. Overall, no differences were noted in feed intake (P=0.091, P=0.845), bodyweight gain (P=0.433, P=0.619), or feed conversion ratio (FCR) (P=0.060, P=0.727) in either Experiment (Experiment 1 and Experiment 2, respectively). These results indicate that BSFL frass can be an effective and safe feed ingredient option for commercial broiler production.